Vulvo-vaginal atrophy: A new treatment modality using thermo-ablative fractional CO2 laser. Issue 3 (March 2015) - Perino, Antonino; Calligaro, Alberto; Forlani, Francesco; Tiberio, Corrado; Cucinella, Gaspare; Svelato, Alessandro; Saitta, Salvatore; Calagna, Gloria
Highlights Vulvo-vaginal atrophy is a progressive, chronic condition that manifests as involution of the vulvo-vaginal mucous membranes and tissues due to the menopausal drop in estrogen levels. It can worsen over the years and negatively influence quality of life. The use of CO2 laser has been widely adopted in medicine, especially in dermatology and plastic surgery. It consists of a CO2 ray, which generates heat and vaporizes the water content of target cells. Laser technology can be used to achieve vaginal "regeneration" with a minimally invasive procedure, thereby improving elasticity and hydration of the vaginal walls and relieving discomfort in menopausal women. We report our experience about the application of the fractional CO2 Laser treatment to determine the safety and efficacy of this treatment in improving VVA symptoms in post-menopausal women.